Significance of antioxidative defence under long-term Cd stress - Solti, Ádám (Acta Biologica Szegediensis, 2011)
Cadmium is a highly toxic heavy metal which causes strong oxidative stress thereby inactivating PSII and the photosynthetic electron transport. However, plants acclimate to moderate Cd stress under longer treatment. Here, the role of antioxidative defence was studied during this acclimation. Micropropagated poplar plants were treated with 10 μM Cd(NO3)2 from their four-leaf-stage for four weeks. Increase in the malondialdehyde content and in the ratio of inactive, quenching PSII reaction centres (ΦNF) was observed in the first two weeks of the treatment. Starting from the third week both parameters decreased in parallel to the rise in the ascorbate peroxidase activity and B-carotene content, both are important in the antioxidative defence in chloroplasts. Therefore, an acute and an acclimation phase were identified as a consequence of the delay in activation of antioxidative defence mechanisms, the protective role of which is important in the acclimation to moderate Cd stress.